Implementation of ALICE chatbot as domain specific knowledge bot for BRAC U (FAQ bot) - Rahman, Johan (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2012.